Dancers utilize a `whip-like effect` to increase arm angular momentum during multiple-revolution pirouette en dehors - Imura, A.; Iino, Y.; Koike, S. (Sports Biomechanics, 2022)
A pirouette en dehors (PeDh) is multiple turns using the angular momentum generated by swinging the arms with both feet on the ground. The purpose of this study was to investigate how the arm swing facilitates increasing peak angular momenta of both arms during multiple PeDh. Upper body movements in single to six-revolutions clockwise (as seen from above) PeDhs were analysed to determine arm`s angular momentum induced by the individual joint torque, gravitational force and motion-dependent terms. The horizontal abduction and adduction torques of the right and left shoulder joints, respectively, and clockwise torsional torque of the upper torso induced the clockwise angular momentum (CWAM) of the arms in the horizontal plane, about the vertically upward axis. The motion-dependent term induced the CWAMs after joint torques and contributed to the maximum total CWAM of both arms substantially. The CWAMs induced by the motion-dependent term increased with joint torques up to the triple PeDh in the right arm but independently from the left shoulder joint torque up to the sextuple PeDh in the left arm. Using a whip-like motion of the arm, increasing the arm joint torques would not be required necessarily when performing, i.e., more than quaruple PeDhs.